If a=tan⁡27θ−tan⁡θ and b=sin⁡θcos⁡3θ+sin⁡3θcos⁡9θ+sin⁡9θcos⁡27θ, then

If a=tan27θtanθ and b=sinθcos3θ+sin3θcos9θ+sin9θcos27θ, then

  1. A

    a=b

  2. B

    a=2b

  3. C

    b=2a

  4. D

    a+b=2

    Register to Get Free Mock Test and Study Material

    +91

    Verify OTP Code (required)

    I agree to the terms and conditions and privacy policy.

    Solution:

    We have,

          a=tan27θtanθ

    =     a=tan27θtan9θ+tan9θtan3θ+tan3θtanθ    a=sin18θcos27θcos9θ+sin6θcos9θcos3θ+sin2θcos3θcosθ

        a=2sin9θcos27θ+sin3θcos9θ+sinθcos3θa=2b

    Chat on WhatsApp Call Infinity Learn

      Register to Get Free Mock Test and Study Material

      +91

      Verify OTP Code (required)

      I agree to the terms and conditions and privacy policy.